The Origin of Viruses and Somatic Diseases (Global Journal of Medical Research, 2021)
A main genome is the genome of bacteria or, more precisely, the genome of singlecelled prokaryotic microorganisms that appeared on earth 3.5 billion years ago, which marked the beginning of biological life on the earth planet. How the bacteria appeared - there are many assumptions, but the main one is that the earth, like other planets in universe, participated in this creative process. One of the intermediate biological products of the bacterial genome is a human. The action of creating multicellular mammals from single-celled microorganisms that have "gray" matter and are capable of thinking has been going on for millions of years and is still going on today. The question remains: where does this process go - from Homo sapiens to Homo degrading or Homo natural? The significance of the relationship and interdependence between the main genome and the human genome has become particularly acute with the appearance of the SARS-CoV-2 coronavirus (disease X?). Here we will discuss the mechanisms of the emergence of coronavirus as one of the crucial stages of the adaptation process of virus formation from adaptogens and its impact on the further development of mammals, including humans.
Keywords: main genome; SARS-CoV-2; disease X; CRISPR/Cas; adaptogens; vaccine; diagnosis; infection prognosis; concept